Case report: Sclerosed hemangioma of the liver: A diagnostic challenge - Poras, M.; Katsanos, G.; Agrafiotis, A. C.; Demetter, P.; Pezzullo, M.; Lucidi, V. (Frontiers in Surgery, 2022)
Hemangiomas are the most common non-cystic benign hepatic tumors and are usually incidentally discovered during routine radiological examinations. Diagnosis of hepatic hemangiomas with a typical presentation is generally easy at plain and cross-sectional imaging; however it can be complicated when hemangiomas undergo histological changes such as fibrosis. Sclerosed hepatic hemangioma (SHH) is the extreme presentation of this fibrotic process. These atypical lesions can be misdiagnosed for primary hepatic malignancies or metastasis. Their diagnosis is established by histological examination. We report the case of a patient with a sclerosed hepatic hemangioma (SHH) which was misdiagnosed as an intrahepatic cholangiocarcinoma. This article's aim is to draw attention on this infrequent pathology and underline the features of this benign tumor which could suggest its diagnosis prior to surgery in order to avoid unnecessary hepatic resections.